The impact of arthrocentesis with and without hyaluronic acid injection in the prognosis and synovial fluid myeloperoxidase levels of patients with painful symptomatic internal derangement of temporomandibular joint: a randomised controlled clinical trial - YARAT, AYŞEN (WILEY, 2017)
We aimed to assess the relationship between myeloperoxidase (MPO) and internal derangement (ID) of temporomandibular joint (TMJ) and effects of arthrocentesis procedure, either alone or in combination with hyaluronic acid (HA) injection on the prognosis of ID of TMJ. A prospective randomised controlled trial has been conducted through patients, who underwent arthrocentesis for the treatment of ID of TMJ, were randomly divided into two groups. Group SS (n=10) and Group HA (n=14) patients were assigned 09% NaCl solution and sodium hyaluronate intra-articularly, respectively. Synovial fluid samples were assayed for MPO at the time of arthrocentesis and pain visual analogue scale (VAS) and maximum mouth opening (MMO) scores were recorded at pre- and post-operative periods as well as first-week, first-month and third-month intervals. There was a statistically significant decrease in MPO levels between the first to second arthrocenteses only in Group 2 (P=0001). Both VAS scores and MMO measurements decreased in the course of time following arthrocentesis and donot differ between the patients administered HA or SS. Similarly MPO levels do not change significantly between the two groups at either first or second arthrocenteses. In HA group, MPO levels significantly decreased from first to second sessions. In HA group, MPO levels decreased significantly only in patients with clinical success. Arthrocentesis procedure improves both pain VAS and MMO scores in the course of time, but these parameters do not differ between patients receiving either HA or SS. HA significantly reduces levels of MPO in synovial fluid, but SS does not. HA appears to alleviate inflammation inside the TMJ in patients with TMJ-ID.
Keywords: temporomandibular joint; myeloperoxidase; arthrocentesis; hyaluronic acid; CHRONIC CLOSED LOCK; FOLLOW-UP; INFLAMMATORY CYTOKINES; OSTEOARTHRITIS; COLL2-1NO(2); IRRIGATION; DISORDERS; DISEASE; LAVAGE